Preferences for a new vaccine against an emerging infectious disease: A discrete choice experiment among Millennials and Generation Z in Vietnam - Pham, Gam H.; Tran, Quang V.; Bui, Hiep T.; Nguyen, Thoai D.; Vo, Trung Q.; Jedsadayanmata, Arom; Huynh, Bon H.; Sholihat, Nia K. (Narra J, 2025)
The rising threat of emerging infectious diseases (EIDs) highlights the need to understand factors influencing vaccine adoption. The aim of this study was to explore the willingness to vaccinate and vaccine acceptance preferences among Millennials and Generation Z in Vietnam. Convenience sampling was conducted, after which a traditional discrete choice experiment was performed. Participants were tasked with selecting their preferred options from a set of eight vaccination choice tasks, each consisting of two alternatives distinguished by varying degrees of vaccine efficacy, side effects, influential endorsements, trusted sources, and disease susceptibility through literature reviews, expert interviews, and pilot tests. A minimum sample size of 375 participants was recruited via Internet-based and paper-based surveys.  A latent class model was used to explore the heterogeneity in participant preferences, while a mixed logit model was employed to facilitate the computation of the predicted probabilities of vaccine acceptance. Among the 818 included participants, 494 (60.4%) were Millennials generation. The predicted probability of vaccine acceptance was 61.8%, with slight differences between Millennials (62.4%) and Generation Z (61.0%). Four latent classes with significant preference variations were identified. Class 1 (38%) was influenced by vaccine effectiveness, side effects, and health authority recommendations, showing lower opt-out rates. Class 2 (28%) prioritized vaccine effectiveness and authority recommendations but had higher opt-out rates and a stronger religious influence. Class 3 (23%) focused on vaccine effectiveness and side effects, with a tendency to opt-out. Class 4 (11%) valued high vaccine effectiveness and advice from family, with infection risks to family or local areas being significant motivators. Influential voices were more important in Classes 1 and 2, while side effects and effectiveness were prioritized in Classes 3 and 4. In conclusion, Vietnamese Millennials and Generation Z preferred vaccination when the vaccine had 90% efficacy, mild to moderate side effects, endorsements from the Ministry of Health, positive recommendations from family and social networks, and high exposure risks from family members.